STRUGGLE AND CHANGING IDENTITY OF IMMIGRANTS IN JHUMPA LAHIRI’S NOVEL THE NAMESAKE: AN ANALYTICAL STUDY (International Journal of Food and Nutritional Sciences, 2022)
Jhumpa Lahiri’s The Namesake is the novel that gives the life journey of the USA based Indian Diaspora. Hence an honest effort through this paper has been done to study the how different characters in the novel acts as per the time and show their traits in different situation and emerges as true Indian Diaspora. At the same time, the pangs of alienation and adjustment in foreign culture at the cost of leaving one’s own mother land is also systematically analysed. The paper also highlights on how the new generations of Indian Diaspora react to the changing situation and how they adjust themselves as the culture and land change.